Keśava, Saṅghanirmātā - Bhiśīkara, Cã. Pa., 1915- (Bhāratīya Vicāra Sādhanā, 1978)
Biography of Keshav Baliram Hedgewar, 1889-1940, founder of the Rashtriya Swayam Sevak Sangh, a militant Hindu organization in India.